Myelin Oligodendrocyte Glycoprotein Antibody‐Associated Optic Neuritis With Perineuritis Treated With Immunoadsorption Plasmapheresis in a 91‐Year‐Old Woman: A Case Report - Isamu Takai; Yuji Tomizawa; Yasunobu Hoshino; Chikage Kijima; Natsumi Takemura; Naoto Arawaka; Rei Iwamoto; Eitaro Yoshida; Takashi Kyomoto; Kazumasa Yokoyama; Shintaro Nakao; Taku Hatano (Clinical and Experimental Neuroimmunology, 2026)
ABSTRACT Background Myelin oligodendrocyte glycoprotein antibody‐associated disease can occur in older adults, but onset in nonagenarians is uncommon. In this age group, acute or subacute visual loss often requires differentiation from ischemic, diabetic retinal, and glaucomatous disorders. Case Presentation A 91‐year‐old woman presented with subacute bilateral visual loss over 9 days. Ophthalmological examination showed severe bilateral visual impairment, optic disc edema, and visual field constriction. Serum myelin oligodendrocyte glycoprotein antibodies were positive. Contrast‐enhanced orbital magnetic resonance imaging showed bilateral optic nerve enlargement, optic nerve sheath enhancement, and perineural inflammatory changes. Temporal artery ultrasonography showed no halo sign. High‐dose intravenous methylprednisolone followed by oral prednisolone led to limited visual recovery. Further corticosteroid exposure was undesirable because of poorly controlled diabetes. Immunoadsorption plasmapheresis was performed under close monitoring, and visual function improved without bleeding or hemodynamic complications. Delayed corticosteroid effects cannot be excluded, but immunoadsorption plasmapheresis may be an option when further corticosteroid exposure is undesirable in very elderly patients. Conclusions This case describes the diagnostic and therapeutic management of myelin oligodendrocyte glycoprotein antibody‐associated optic neuritis with perineuritis in a nonagenarian. Immunoadsorption plasmapheresis may be considered in selected elderly patients when corticosteroid response is insufficient or further corticosteroid exposure is clinically difficult.